Novel polymer-inorganic solid-state reaction for the synthesis of CdS nanocrystallites - Kanade, K. G.; Hawaldar, Ranjit R.; Pasricha, R.; Radhakrishnan, S.; Seth, T.; Mulik, Uttam P.; Kale, B. B.; Amalnerkar, Dinesh P. (Materials Letters, 2005)
We offer a novel polymer-inorganic solid-state reaction route for the in situ generation of nanochalcogenide semiconductor in the network of polymer which itself acts as a chalcogen source. We have exemplified feasibility of this route by reacting CdI2 with engineering thermoplastic polyphenylene sulphide (PPS). These two reactants in 1:1 and 10:1 molar ratios were simply heated at the crystalline melting temperature of PPS. The resultant products were characterized by X-ray diffractometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM, with selected area electron diffraction). The prima facie observations revealed the formation of cubic nanocrystallites of US with the particle size ranging from 6 to 20 nm entrapped in modified (cyclized) PPS matrix when the reactants were taken in 10:1 molar ratio. A tentative mechanism has been suggested for such hitherto unattempted solid-state reaction. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdS nanocrystallites; Semiconductor; solid-state reaction; Thermoplastic polymer matrix

Conducting polymer based hybrid nano-composites for enhanced corrosion protective coatings - Patil, R. C.; Radhakrishnan, S. (Progress in Organic Coatings, 2006)
Hybrid composite coatings containing zinc oxide (ZnO) and polyaniline (PANI) as nano-additives dispersions were prepared with poly(vinyl acetate) (PVAc) as the major matrix. The steel plates dip-coated with these formulations were tested for corrosion protection by immersion in saline water over long periods. The Tafel plots for the determination of open circuit potential (OCP) and corrosion current (I-corr) were recorded. The coatings containing both ZnO and PANI showed improved corrosion resistance as compared to the single component coating. The I-corr values of PVAc-ZnO-PANI are found to be two-order magnitude lower than that of PVAc and PVAc-ZnO coatings. The results are explained on the basis of enhancement in barrier properties due to nano-particulate additives in PVAc-ZnO-PANI film together with the redox behaviour of PANI and protective oxide layer formation near the substrate. (C) 2006 Elsevier B.V All rights reserved.
Keywords: Coatings; corrosion; nano-additives; polyaniline; ZnO

Response characteristics of conducting polypyrrole bi-layer actuators: role of backing layer polymer - Radhakrishnan, S.; Kar, Swarnendu B. (Sensors and Actuators B-Chemical, 2006)
The response of a bi-layer conducting polymer-based actuator has been studied with respect to various parameters such as backing layer thickness, backing layer modulus, applied voltage, etc. The bending angles for the bi-layer actuators made by depositing, conducting polypyrrole (PPy) films on backing layers using LDPE/LLDPE, SBS, Hytrel, PP, PET materials have been compared. The response of the bi-layer actuators indicates that there is optimum for the backing layer thickness as well as its material modulus together with the thickness of the conducting polymer at which the maximum bending is observed. Other geometrical parameters such as a length to width ratio also influence the response of these actuators and have to be chosen properly for the best actuator performance. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: actuator; bi-layer; conducting polymer; polypyrrole; response

Role of dopant ions in electrocatalytic oxidation of methanol using conducting polypyrrole electrodes - Radhakrishnan, S.; Adhikari, Arindam (Journal of Power Sources, 2006)
Conducting polypyrrole electrodes obtained by electro-polymerization of pyrrole on vacuum metallized glass substrates are modified by doping with a range of metal halides as dopant ions having different electronegativity. Electro-oxidation of methanol using these electrodes is studied by means of cyclic voltammetry in 0.1 M HCiO(4) as supporting electrolyte. It is found that the electronegativity of the dopant ion plays a very important role in the electrocatalytic activity. Polypyrrole doped with zirconium chloride gives the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. The results are explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which is associated with the acceptor state created by the dopant in the semi-conducting polymer. (c) 2005 Published by Elsevier B.V.
Keywords: conducting polymers; electrocatalysis; fuel cells; Methanol oxidation; polypyrrole

Fabrication of MEMS composite-polymer gas sensor arrays for electronic nose - Pant, B. D.; Kutnar, Mahesh; Lakshmi, Subha; Arora, Anil; Prasad, Mahanth; Sharma, Akshdeep; Patel, Mohan; Radhakrishnan, S.; Dwivedi, V. K. (Indian Journal of Pure & Applied Physics, 2007)
Sensor arrays capable of sensing different gases combined with a sampling system and a means of pattern classification and recognition comprise a basic system for an `Electronic Nose' In the present work, a complete process for the fabrication of micro-cavities with sensing electrodes and volumes ranging from 2.5 to 12 nano-liters for the development of polymer gas sensors has been reported. An array of eight sensing cells in four sizes have been fabricated using SU-8 negative tone resist through UV-LIGA process developed at CEERI, Pilani. The length and width of the SU-8 cavities are: 250 x 250, 300 x 300, 500 x 500 and 500 x 600 micron and the depth of each of them was optimized to be 40 micron. These cavities filled with different polymer composites comprise the basic sensing cells for a variety of gases. The current paper presents the salient features of the fabrication process in detail and the results obtained in ethanol and methanol ambient using a polymer composite developed through dissolution of styrene and polyaniline in PMMA. A number of other composites such as Pc-Ppy, Pr-Ppy, Fc(+)-PPy have also been synthesized and tested for a high sensitivity in carbon monoxide.
Keywords: composite polymer; conducting polymer; electronic nose; polymer gas sensor; selectivity; sensitivity; sensor array

High-temperature, polymer-graphite hybrid composites for bipolar plates: effect of processing conditions on electrical properties - Radhakrishnan, S.; Ramanujam, B. T. S.; Adhikari, Arindam; Sivaram, S. (Journal of Power Sources, 2007)
High-temperature thermoplastic-graphite composites are prepared using polyphenylene sulfide (PPS) and polyether sulfone (PES) containing natural graphite powder. All samples are prepared by high pressure compaction and heating to high temperatures. The effect of a third additional conducting component on the electrical resistance of these composites is studied. A low resistance of the order of 0.1 Omega can be obtained even for a graphite concentration of 50% by addition of the third component. The effect of a mixing/blending technique on the anisotropy of conductivity is investigated. Solution blending of PES with graphite leads to lower anisotropy values than powder mixing and compression moulding. The samples when exposed continuously to a working temperature of 100 degrees C give a small but significant reduction in electrical resistance. X-ray diffraction studies on composites prepared by different techniques indicate that there is restructuring and crystallite re-orientation of the graphite phase in the samples. A large reduction in the crystallite size is observed for samples prepared by solution blending while re-orientation occurs after heat treatment. The changes in electrical properties can be correlated with these structural transformations in the composites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bipolar plates; conducting polymer; fuel cell; graphite composites; hybrid materials; polyether sulfone; polypherylene sulfide

Role of ionic diffusion in polymer gel mediated growth (PMG) technique for the synthesis of nanoparticulate fillers - Sonawane, Pradip S.; Biradar, Santoshkumar S.; Radhakrishnan, S.; Kulkarni, B. D. (Materials Chemistry and Physics, 2007)
Polymer mediated growth (PMG), which forms an important method for synthesis of nanoparticles, has one of the ions bound by polymer matrix while the other is allowed to diffuse and react to form desired compound. The exact role of ionic diffusion in the formation of nanoparticles has been investigated by taking specific case studies. Typically calcium carbonate, calcium phosphate and calcium sulfate have been formed in nano-size by PMG route using polyacrylamide gel. The extent of cross-linking of the polymer matrix in the formation of gel, affects the diffusivity of ions into polymer matrix and the size of particles formed. The rates of diffusion for different extents of cross-linking of polymer are estimated during the synthesis of nanoparticles using Fick's law. The inter-correlation between the particle size formation and the diffusion length has been clearly brought out in these studies. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ionic diffusion; nanoparticulate fillers; polymeric gels

Adsorption of sulfonated dyes by polyaniline emeraldine salt and its kinetics - Mahanta, Debajyoti; Madras, Giridhar; Radhakrishnan, S.; Patil, Satish (Journal of Physical Chemistry B, 2008)
A method for the removal of anionic (sulfonated) dyes from aqueous dye solutions using the chemical interaction of dye molecules with polyaniline is reported. Polyaniline (PANI) emeraldine salt was synthesized by chemical oxidation. Sulfonated dyes undergo chemical interactions with the charged backbone of PANI, leading to significant adsorption of the dyes. This phenomenon of selective adsorption of the dyes by PANI is reported for the first time and promises a green method for removal of sulfonated organics from wastewater. The experimental observations from UV-vis spectroscopy, X-ray diffraction, and conductivity measurements rule out the possibility of secondary doping of polyaniline salt by sulfonated dye molecules. A possible mechanism for the chemical interaction between the polymer and the sulfortated dye molecules is proposed. The kinetic parameters for the adsorption of sulfonated dyes on PANI are also reported.

Development of nanofibrous morphology in LDPE/LLDPE/PP blends and its effect on mechanical properties of blend films - Sonawane, Pradip S.; Radhakrishnan, S.; Bhangale, J. A.; Gadhavi, A. L.; Khare, Anagha (Journal of Applied Polymer Science, 2008)
Nanofibrous morphology has been observed in ternary blends of low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and isotactic polypropylene (PP) when these were melt-extruded via slit die followed by hot stretching. The morphology was dependent on the concentration of the component polymers in ternary blend LDPE/LLDPE/PP. The films were characterized by wide angle X-ray diffraction (XRD), scanning electron microscopy (SEM), and testing of mechanical properties. The XRD patterns reveal that the P phase of PP is obtained in the as-stretched nanofibrillar composites, whose concentration decreases with the increase of LLDPE concentration. The presence of PP nanofibrils shows significant nucleation ability for crystallization of LDPE/LLDPE blend. The SEM observations of etched samples show an isotropic blend of LDPE and LLDPE reinforced with more or less randomly distributed and well-defined nanofibrils of PP, which were generated in situ. The tensile modulus and strength of LDPE/LLDPE/PP blends were significantly enhanced in the machine direction than in the transverse direction with increasing LLDPE concentration. The ultimate elongation increased with increasing LLDPE concentration, and there was a critical LLDPE concentration above which it increased considerably. There was a dramatic increase in the falling dart impact strength for films obtained by blow extrusion of these blends. These impressive mechanical properties of extruded samples can be explained on the basis of the formation of PP nanofibrils with high aspect ratio (at least 10), which imparted reinforcement to the LDPE/LLDPE blend. (C) 2007 Wiley Periodicals, Inc.
Keywords: linear low density polyethylene; low density polyethylene; mechanical properties; melt-extruded films; nanofibrous morphology; polypropylene; ternary blends

Adsorption and desorption kinetics of anionic dyes on doped polyaniline - Mahanta, Debajyoti; Madras, Giridhar; Radhakrishnan, S.; Patil, Satish (Journal of Physical Chemistry B, 2009)
In this study, we report an approach for the adsorption and desorption of anionic (sulfonated) dyes from aqueous solution by doped polyaniline. In this study, we have synthesized PANI with two dopants, namely, p-toluenesulfonic acid (PTSA) and camphorsulfonic acid (CSA), and used these to adsorb various dyes. It was found that the doped PANI selectively adsorbs anionic dyes and does not adsorb cationic dyes. The adsorption of anionic dyes causes the variation in electrical conductivity of PANI, indicating its potential as a conductometric sensor for these dyes at very low concentration. The adsorbed dyes were desorbed from the polymer by using a basic aqueous solution. The adsorption and desorption kinetics of the dye in the presence of doped PANI were also determined.

CO sensor based on polypyrrole functionalized with iron porphyrin - Paul, Santhosh; Amalraj, Francis; Radhakrishnan, S. (Synthetic Metals, 2009)
Polypyrrole (PPy) was chemically functionalized with 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron(III) chloride (FeTPPCl) with special interest on noxious carbon monoxide (CO) gas in ppm level. Controlled functionalization of PPy was achieved with incorporation of various concentrations of porphyrin. The resulted semiconducting material was well characterized by different techniques such as UV-vis spectroscopy, FTIR, GFAAS, XRD, and EDAX. The functionalized polypyrrole material on interdigitated electrode was experienced an immediate increase in resistance when exposed to carbon monoxide gas at very low concentration. The CO gas interacted very fast with the FeTPPCl functionalized PPy at room temperature (RT) and then slowly saturated. The response of these materials was not unidirectional, but reverses to the original resistance level when CO was removed from the test chamber. The highest response factor (Delta R/R(0) x 100) and lowest response time (t(50)) obtained are 12 and 169s, respectively. An optimum level of doping (1 mol% of FeTPPCl) was established for the highest sensitivity and the detection level is as low as 100ppm. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; Fe(III) porphyrin; polypyrrole

Conducting polyaniline-nano-TiO2 composites for smart corrosion resistant coatings - Radhakrishnan, S.; Siju, C. R.; Mahanta, Debajyoti; Patil, Satish; Madras, Giridhar (Electrochimica Acta, 2009)
Coatings prepared from polyaniline-nano-TiO2 particles synthesized by in situ polymerization were found to exhibit excellent corrosion resistance much superior to polyaniline (PANI) in aggressive environments. The corrosion Studies were carried out on steel plates coated with these formulations containing 10 wt% polyaniline prepared with different concentrations of nano-TiO2. The electrochemical impedance spectroscopy was studied at periodic intervals during exposure to hot saline (65 degrees C) conditions for prolonged durations over a period of 90 h. The open circuit potential (OCP) was found to shift with time from -0.38 V SCE to more anodic side (-0.2 V SCE) much above that of bare steel (-0.5 VSCE). The presence of nano-TiO2 was found to be vital in the prevention of corrosion and the shift of OCP to anodic side. From these data, one could envisage more than 100 times improvement in the corrosion resistance especially for polyaniline prepared with 4.18 wt% nano-TiO2. The exceptional improvement of performance of these coatings has been associated with the increase in barrier to diffusion, prevention of charge transport by the nanosize TiO2, redox properties of polyaniline as well as very large surface area available for the liberation of dopant due to nano-size additive. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Anticorrosion; Coating; conducting polymer; Nano-composite; Titanium dioxide

Epoxy powder coatings containing polyaniline for enhanced corrosion protection - Radhakrishnan, S.; Sonawane, Narendra; Siju, C. R. (Progress in Organic Coatings, 2009)
Incorporation of polyaniline (PANI) in epoxy type powder coating formulations has not been attempted earlier. Using specific grade of PANI with low doping, it can be incorporated in epoxy powder coating formulations by twin screw extrusion process. The powder formulations were deposited on steel substrates by electrostatic spray coating at -60 W and baked at 140 degrees C for 20 min. These were extensively tested for corrosion resistance by exposure to hot saline conditions followed by electrochemical impedance spectroscopy and also salt spray testing. PANI incorporated coatings showed no deterioration even after 1400 h of hot (65 degrees C) saline treatment. The coatings intentionally scratched also exhibited self healing property and there was no rust formation even after prolonged exposure to hot saline conditions. These results could be explained on the basis of additional crosslinking due to PANI, as confirmed by DSC results, which gave rise to improved barrier property and self healing was associated with the scavenging of ions by PANI which prevented corrosion of the underlying substrate. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Corrosion resistance; Epoxy; polyaniline; Powder coating

Influence of dopant ions on properties of conducting polypyrrole and its electrocatalytic activity towards methanol oxidation - Adhikari, Arindam; Radhakrishnan, S.; Patil, Rahul (Synthetic Metals, 2009)
The polypyrrole (PPy) films were deposited on vacuum metallized substrates by electro-oxidation of pyrrole monomer. These electrodes were then modified with a range of metal halides having different electronegativities. The modified polypyrrole electrodes were employed to investigate electrocatalytic activity towards methanol electrochemical oxidation by means of cyclic voltammetry in 0.1 M HClO(4) as supporting electrolyte. It was found that the electronegativity of the dopant ion incorporated in the PPy film governs the electrocatalytic activity towards methanol oxidation. Among different dopant anions used in the present work, the PPy doped with zirconium chloride gave the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. Electrical property and the charge created due to doping in the polymers were measured using X-ray photoelectron spectroscopy (XPS) and Electron spin resonance spectroscopy (ESR). Electrocatalytic activity of the modified electrodes was correlated with various factors obtained from different polymer characterization experiments. The results were explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: charge transfer; electrocatalyst; ESR; Metal halide dopant; Methanol oxidation; polypyrrole; XPS

Polypyrrole functionalized with ferrocenyl derivative as a rapid carbon monoxide sensor - Paul, Santhosh; Chavan, Nayaku; Radhakrishnan, S. (Synthetic Metals, 2009)
A rapid carbon monoxide detection system was developed with the electrochemical functioncalization of polypyrrole (PPy) with ferrocenylmethyltrimethylammonium iodide (FTMA-I) as a co-dopant exhibits very high sensitivity to ppm levels of carbon monoxide gas and fast recovery under normal dry room temperature conditions. The co-dopant was synthesized mainly to incorporate into PPy electrochemically to modify the properties in order to sense carbon monoxide (CO) gas. The FTMA-I doped PPy exhibited the characteristics oxidation/reduction peaks for ferrocene in its cyclic voltammograms. The modified PPy films deposited on interdigited electrodes gave rapid sensitivity within a second to 300 ppm carbon monoxide gas and good sensitivity factor was observed even at 4 mmol of the functional groups in the polymer for 300 ppm carbon monoxide gas. This material detected the CO gas concentration as low as 100 ppm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: carbon monoxide; Chemical sensor; conducting polymer; polypyrrole

Polyethersulfone-expanded graphite nanocomposites: charge transport and impedance characteristics - Ramanujam, B. T. S.; Mahale, Rajashree Y.; Radhakrishnan, S. (Composites Science and Technology, 2010)
Polyethersulfone (PES)-expanded graphite nanocomposites have been prepared by solution blending route after sonicating expanded graphite in dichloromethane. It has been observed that ultrasonication results in nanosheets formation leading to a low percolation threshold of 3 wt.%. At 5 wt.% filler loading the conductivity is of the order of 10(-2) S/cm. Hopping type of charge transport occurs at 3.2 wt.% expanded graphite in PES below which capacitive effects couple. The effective dielectric constant at low frequency increases with filler concentration. Impedance measurement has been carried out to evaluate interfacial capacitance which, for 3.2 wt.% expanded graphite addition in PES, increases to 110 pF from 32 pF for 1 wt.% expanded graphite in the polymer. DSC analysis shows an increment of 12 C in the T(g) of PES with 3 wt.% expanded graphite suggesting interaction between the polymer and filler. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Electrical properties; Modeling; Polymers; Scanning/transmission electron microscopy (STEM)

Dopant induced effect on electrocatalytic reduction of nitrobenzene using conducting polypyrrole thin film electrodes - Adhikari, Arindam; Radhakrishnan, S. (Journal of Applied Polymer Science, 2011)
Conducting polypyrrole electrodes were prepared by electrochemical polymerization of pyrrole on vacuum-metallized glass substrates. These electrodes were modified by doping with a range of metal halides as dopant ions having different electronegativity. Electrochemical reduction of nitrobenzene using these electrodes was studied by means of cyclic voltammetry technique in acetonitrile medium containing aqueous HClO(4) (0.1M) as supporting electrolyte. It was found that the electronegativity of the dopant ion played a very important role in the electrocatalytic activity. Polypyrrole doped with nickel chloride gave the highest anodic current at the reduction potential of nitrobenzene. The results were explained on the basis of charge transfer efficiency at the electrode-electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 719-724, 2011
Keywords: charge transfer; conducting polymer; Doping; electrocatalysis; nitrobenzene; polypyrrole; reduction

Polyaniline modified electrodes for detection of dyes - Mahanta, Debajyoti; Munichandraiah, N.; Radhakrishnan, S.; Madras, Giridhar; Patil, Satish (Synthetic Metals, 2011)
Polyaniline (PANI) is one of the most extensively used conjugated polymers in the design of electrochemical sensors. In this study, we report electrochemical dye detection based on PANI for the adsorption of both anionic and cationic dyes from solution. The inherent property of PANI to adsorb dyes has been explored for the development of electrochemical detection of dye in solution. The PANI film was grown on electrode via electrochemical polymerization. The as grown PANI film could easily adsorb the dye in the electrolyte solution and form an insulating layer on the PANI coated electrode. As a result, the current intensity of the PANI film was significantly altered. Furthermore, PANI coated stainless steel (SS) electrodes show a change in the current intensity of Fe(2+)/Fe(3+) redox peaks due to the addition of dye in electrolyte solution. PANI films coated on both Pt electrodes and non-expensive SS electrodes showed the concentration of dye adsorbed is directly proportional to the current intensity or potential shift and thus can be used for the quantitative detection of textile dyes at very low concentrations. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electrochemical sensor; Emeraldine base; Emeraldine salt; polyaniline

Effect of the surface roughness of conducting polypyrrole thin-film electrodes on the electrocatalytic reduction of nitrobenzene - Adhikari, Arindam; Radhakrishnan, S.; Vijayan, M. (Journal of Applied Polymer Science, 2012)
Conducting polypyrrole (PPy) thin-film electrodes were prepared by the electropolymerization of pyrrole on gold-coated glass plates. Films of various roughnesses were obtained by the variation of the scan rates during electropolymerization. These thin films were modified by doping with 6mM of the dopant NiCl2. The surface morphology of the films was studied by scanning electron microscopy and atomic force microscopy (AFM), which suggested films prepared with a high scan rate were rougher in nature than the films produced with a low scan rate. The electrocatalytic reduction of nitrobenzene was carried out with these electrodes with the cyclic voltammetry technique in acetonitrile containing 0.1M HClO4 as a supporting electrolyte. The various results obtained show that the conducting PPy thin-film electrodes were catalytically active toward the electroreduction process. The modified PPy film electrodes doped with NiCl2 were more active toward nitrobenzene electroreduction than the PPy film alone. The results indicate that the roughness of the films played a very important role in determining their catalytic activity. The PPy films that were more rough in nature were catalytically more active than the smooth films; this may have been due to the availability of more reactive sites in the case of rough films. The apparent diffusion coefficients of the PPy film electrodes were also calculated. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: atomic force microscopy (AFM); conducting polymers; Diffusion; surface modification; Thin films

Analysis of electrical and thermal conductivities of polyethersulfone-graphite based hybrid nanocomposites - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, Shripad D. (Macromolecular Research, 2017)
Polyethersulfone (PES)-7 wt% graphite- x wt% filler (carbon black (CB), carbon nanofiber (CNF), expanded graphite (ExGr)) hybrid composites are synthesized by solution blending route. The electrical percolation threshold in hybrid composites varies exponentially with the aspect ratio of the second conducting filler. The aspect ratio of the second conducting filler has been found to vary in the order CB < CNF < ExGr. The percolation threshold is identified at 0.05 wt%, 0.4 wt%, 1.3 wt% for ExGr, CNF and CB added PES-7 wt% graphite composites. Through plane thermal conductivity of PES-x wt% graphite-y wt% CB (x=10, 20, 30, 40, 50, 60, y=0, 3, 7) hybrid composites has been found to increase with the addition of CB. Thermal conductivity has been increased to 0.42 W/m-K when 7 wt% CB is added to PES-60 wt% graphite from 0.2 W/m-K. Reduction of interparticular distance with the increased loading of CB facilitates better thermal transport. Aspect ratios of second conducting fillers have been found out from transmission electron microscopy and scanning electron microscopy analysis.

Polyphenylene sulfide- expanded graphite nanocomposites: processing route dependent electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Polyphenylene sulfide (PPS)-expanded graphite (ExGr) conducting nanocomposites have been prepared by powder mixing and in situ polymerization routes after sonicating ExGr particles in acetone. Synthesized PPS has been used to make powder mixed composites. The powder mixed composites exhibit a percolation threshold of 3 wt% due to the formation of graphite nanosheets. When PPS-ExGr composites are prepared by in situ polymerization route, very low electrical percolation threshold less than 0.5 wt% ExGr is obtained. The low percolation threshold obtained is attributed to better dispersion of ExGr nanosheets in the polymer matrix when compared to powder mixed composites. The synthesized PPS has been characterized by X-ray diffraction, differential scanning calorimetry, and infrared spectroscopy. The formation of graphite nanosheets has been confirmed by transmission and scanning electron microcopy analysis.

Polypropylene-based conducting nanocomposites: effect of aspect ratio of second conducting filler on the electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Powder-mixed polypropylene (PP)-graphite binary composites exhibit an electrical percolation threshold at 10 wt% graphite signifying insulator-semiconductor transition. Three conducting fillers such as carbon black (CB), sonicated expanded graphite (s-ExGr), and carbon nanofiber (CNF) are mixed with PP-7 wt% graphite binary composites. The electrical percolation threshold has been found to have inverse relation to the aspect ratio of second conducting fillers in hybrid composites. The aspect ratio of second conducting fillers varies in the order CB < ExGr < CNF. The electrical percolation threshold is found to vary for the hybrid composites as 2.2 wt% for CB addition, 0.75 wt% for ExGr addition, and 0.2 wt% for CNF addition in the PP-7 wt% graphite binary composites. When the aspect ratio of second conducting fillers increases, they reduce the barrier for the charge transport. The second conducting fillers occupy the interspace of graphite and alternating current studies show that the effective dielectric constant increases with the concentration of second conducting filler in the hybrid composites. The composites are characterized by transmission electron microscopy and scanning electron microscopy. Melt-crystallized PP-7 wt% graphite-CNF composites exhibit higher percolation threshold due to decrease in the polymer viscosity which increases the interparticulate distance.
Keywords: carbon nanofiber; Conducting polymer composites; Electrical properties; graphite nanosheets; hybrid composites; percolation; scanning; transmission electron microscopy

High performance and enhanced stability of Mn-Co3V2O8 coral-like structure for supercapacitor applications - Venkatesan, Sethuraman; Rajkumar, Palanisamy; Radhika, Govindaraju; Iyer, Maalavika S.; Manigandan, Ramadoss; Rajaiah, Dhilip Kumar; Radhakrishnan, S.; Raman, Sasikumar; Marimuthu, Senthilkumaran; Kim, Jinho (ACS Applied Energy Materials, 2025)
This study explores Mn-doped Co3V2O8 as a promising electrode material for high-performance supercapacitors. Mn doping significantly enhances the electrochemical properties of Co3V2O8, resulting in improved specific capacitance and cycling stability. Structural characterization reveals a coral-like morphology that increases the active sites and facilitates efficient charge transport and ion diffusion. Electrochemical tests show an impressive specific capacitance of 2352 F g(-1) in 2 M KOH at 1 A g(-1). For the assembled MCV5//AC asymmetric supercapacitor device, it has a high capacitance retention of 87.6% and a high Coulombic efficiency of 96% over 5000 cycles. The developed asymmetric MCV5/AC supercapacitor device achieved an energy density of 45 Wh kg(-1) and a power density of 750 W kg(-1). These findings establish Mn-doped Co3V2O8 as a durable and efficient electrode material, offering valuable insights into the relationship between the morphology and electrochemical performance. This work provides a foundation for the development of advanced materials for sustainable energy storage applications
Keywords: Co3V2O8; Electrode material; Energy storage; stability; supercapacitor